2020
DOI: 10.1108/mhrj-09-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of day treatment for eating disorders: are improvements maintained at 12-month follow-up?

Abstract: Purpose This study aimed to investigate the effectiveness of a specialist UK day treatment programme (DTP), in terms of whether improvements in eating disorder symptomology and psychosocial impairment achieved at discharge were maintained at 6-month and 12-month follow-ups. Design/methodology/approach A total of 69 patients (aged 16+) with eating disorders who had received treatment in the DTP were reviewed at 6-month and 12-month follow-ups, using demographic, physiological and psychological measures. Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that DTPs result in greater improvements in psychological symptoms relating to the Eating Disorder inventory, BMI, and depression and self-esteem when compared to outpatient treatments [ 4 ]. Other studies identified that these changes were maintained at 6 and 12-month follow-ups, supporting the effectiveness of DTPs [ 5 ]. Further long term outcomes related to BMI, relapse and readmission rates favor DTPs over in patient admission, endorsing the need for widespread use of these programs [ 5 ].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have demonstrated that DTPs result in greater improvements in psychological symptoms relating to the Eating Disorder inventory, BMI, and depression and self-esteem when compared to outpatient treatments [ 4 ]. Other studies identified that these changes were maintained at 6 and 12-month follow-ups, supporting the effectiveness of DTPs [ 5 ]. Further long term outcomes related to BMI, relapse and readmission rates favor DTPs over in patient admission, endorsing the need for widespread use of these programs [ 5 ].…”
Section: Introductionmentioning
confidence: 73%
“…Other studies identified that these changes were maintained at 6 and 12-month follow-ups, supporting the effectiveness of DTPs [ 5 ]. Further long term outcomes related to BMI, relapse and readmission rates favor DTPs over in patient admission, endorsing the need for widespread use of these programs [ 5 ].…”
Section: Introductionmentioning
confidence: 73%